Identifying Local Community’s Empowerment in Developing Sustainable Tourism in Pahawang Island, Pesawaran Regency, Lampung Province - Isye Susana Nurhasanah (Journal of Science and Applicative Technology, 2018)
One of the problems on current road infrastructure development in Indonesia is the difficulty of getting road data and information. For example, data and information, which related on sustainable road infrastructure development. Moreover, some of road authorities did not realize that data is important element in the cycle process of road infrastructure development. Inaccurate road data will decrease the quality of road budgeting and programming, on the other hand it will affect the period service of road itself. The good road data could support sustainable road by providing the road value such as historical, current condition, and prediction. Indonesian Road Data Center Operations (IRODCO) is a concept of integrated road database storage. Collaborate data from Indonesian road authority (Ministry of Public Work and Housing, Ministry of Transportation, National Police and Local Government) can be stored, processed and managed to be a value-added information. IRODCO will provide data and information easily and quickly, for supporting the sustainable development of road infrastructure. This paper will explain the background of IRODCO concept, type of road database, the architecture, and how this concept will be implemented in Indonesia, particularly for supporting the sustainable road infrastructure development.